Ximenia americana L: Caracterização química e atividade anti-Candida in vitro e in vivo - FARIAS, Josivan Regis (2022)
Yeasts of the genus Candida are among the fungal species of greatest interest in human health, because in addition to being commensal microorganisms, they are also the microorganisms most frequently isolated in different sites of fungal infection, being classified as opportunistic. The various challenges in therapy motivate the search for new biomolecules with anti-Candida activity. Thus, given the alternatives used by the population, natural products are highlighted, especially those from medicinal plants, with Ximenia americana as a species of interest in the treatment of different diseases. The present study investigated the presence of chemical constituents and the anti-C'andida albicans, C. krusei and C. parapsilosis effect of the stem bark extract of American X. (EEXA), focusing on the action on some virulence factors. The study also aimed to evaluate the acute toxicity of the extract and its action on lethal infection by C. albicans in Tenebrio molitor larvae. Chemical analysis was performed by High Performance Liquid Chromatography (HPLC-DAD) and Liquid Chromatography Coupled with Mass Spectrometry (LC-ESI-IT/MS). The anti-Candida activity was evaluated by agar diffusion, determination of minimum inhibitory concentration (MIC), minimum fungicidal concentration (CFM) and inhibition of virulence factors, such as adhesion, biofilm and production of phospholipase and proteinase exoenzymes. The toxicity of the extract was evaluated in vivo on T. molitor larvae. Larvae were also used to evaluate the effects of EEXA on survival after lethal C. albicans infection. In the EEXA, flavonoids, phenolic compounds, were identified, and catechin derivatives were found more frequently. Regarding the anti-Candida activity, EEXA showed variable inhibition zones according to the standard and clinical strains of C. albicans (3.0+3.0 and 15.7+0.57 mm), C. krusei (5 .0+1.7 and 11.3+0.6 mm) and C. parapsilosis (4.7+1.5 and 11.7+0.6 mm). EEXA inhibited the growth of all fungal species tested with variable MIC/CFM values, indicating fungicidal action for the extract. Treatment with EEXA inhibited the adhesion of C. albicans and C. parapsilosis and the biofilm of all tested species. However, it was only effective in inhibiting the production of phospholipase and proteinase exoenzymes in some samples when used in the highest concentrations, most of the time. In in vivo assays, EEXA showed low toxicity to T. molitor larvae with an LD50 of 50 mg/Kg. The extract treatment increased the survival of animals lethally infected with C. albicans. We conclude that EEXA has a fungicidal action against C. albicans, C. krusei and C. parapsilosis, due to its direct action on fungi and the inhibition of virulence factors, which may also explain its action in increasing the survival of lethally infected larvae. with C. albicans. We infer that the anti-Candida spp. observed is related to the presence of catechins and their derivatives, considering the biological properties of these compounds.